2022
DOI: 10.1167/iovs.63.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Dose of ERCC8 Protein Caused by a Frameshift Mutation Is Associated With Keratoconus With Congenital Cataracts

Abstract: Purpose The purpose of this study was to identify a new candidate gene for keratoconus and congenital cataracts and further investigate its underlying pathogenic mechanisms. Methods This study, using a Chinese family with keratoconus and congenital cataracts, 262 patients with sporadic keratoconus, and 20 patients with sporadic congenital cataract as subjects, used clinical and genetic analysis and in vitro cell experiments to detect genetic mutations and further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…A study carried out by Sarraf et al in 2012 showed that AMN represented an ischaemic phenomenon and can be categorized in two distinct types based on the site of ischaemia in relation to the OPL [ 16 ]. With the advent of OCT-A, more insight was gained into the pathophysiology behind the two entities with hypotheses suggesting that the two diseases may be related in view of similar microvascular changes detected on imaging [ 1 , 17 ]. Type I AMN is characterized by hyperreflectivity in the inner nuclear layer (INL) on OCT whilst type II AMN, as depicted in this case report, is associated with hyperreflectivity in the ONL with the INL-OPL junction being the anatomical cut-off, suggesting that the deep capillary plexus could be the main target of the ischaemic event [ 1 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study carried out by Sarraf et al in 2012 showed that AMN represented an ischaemic phenomenon and can be categorized in two distinct types based on the site of ischaemia in relation to the OPL [ 16 ]. With the advent of OCT-A, more insight was gained into the pathophysiology behind the two entities with hypotheses suggesting that the two diseases may be related in view of similar microvascular changes detected on imaging [ 1 , 17 ]. Type I AMN is characterized by hyperreflectivity in the inner nuclear layer (INL) on OCT whilst type II AMN, as depicted in this case report, is associated with hyperreflectivity in the ONL with the INL-OPL junction being the anatomical cut-off, suggesting that the deep capillary plexus could be the main target of the ischaemic event [ 1 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of OCT-A, more insight was gained into the pathophysiology behind the two entities with hypotheses suggesting that the two diseases may be related in view of similar microvascular changes detected on imaging [ 1 , 17 ]. Type I AMN is characterized by hyperreflectivity in the inner nuclear layer (INL) on OCT whilst type II AMN, as depicted in this case report, is associated with hyperreflectivity in the ONL with the INL-OPL junction being the anatomical cut-off, suggesting that the deep capillary plexus could be the main target of the ischaemic event [ 1 , 17 ]. The absence of capillary cross-sections at the INL/OPL junction and the presence of a draining venule crossing the INL appear to be more indicative of a type II lesion [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also one of the most frequent causes of corneal transplantation ( Sarezky et al, 2017 ). Although the exact cause of KC is still unclear in most patients, the genetic, environmental, and behavioral factors were reported to be associated with its pathogenesis ( Ferrari and Rama, 2020 ; Hao et al, 2022 ; Santodomingo-Rubido et al, 2022 ). Recently, several studies have reported that oxidative stress plays an important role in the development of KC ( Navel et al, 2021 ; Vallabh et al, 2017 ), and mitochondria have been implicated in the pathogenesis of KC due to its crucial role in oxidative stress ( Roy et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several candidate genes or variants associated with KC have subsequently been identified. [11][12][13] However, some genes or variants exhibited different associations in different populations, indicating genetic heterogeneity in KC.…”
mentioning
confidence: 99%